2018
DOI: 10.3390/su10051322
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Utilization of Wheat Straw Ash in Cement-Based Composites

Abstract: The open burning of biomass residue constitutes a major portion of biomass burning and leads to air pollution, smog, and health hazards. Various alternatives have been suggested for open burning of crop residue; however, each of them has few inherent drawbacks. This research suggests an alternative method to dispose wheat straw, i.e., to calcine it in a controlled environment and use the resulting ash as a replacement of cement by some percentage in cement-based composites. When wheat straw, an agricultural pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 59 publications
4
23
1
3
Order By: Relevance
“…When ashes obtained from agricultural by-products are used in cement-based materials, they resolve the matters of sustainability as well as create more durable concrete by acting as pozzolans [17,18]. Research studies that have been conducted on bagasse ash and RHA have shown significantly viable results.…”
Section: Introductionmentioning
confidence: 99%
“…When ashes obtained from agricultural by-products are used in cement-based materials, they resolve the matters of sustainability as well as create more durable concrete by acting as pozzolans [17,18]. Research studies that have been conducted on bagasse ash and RHA have shown significantly viable results.…”
Section: Introductionmentioning
confidence: 99%
“…Rice straw ash (RSA) has been characterized and used to replace 10% and 25% OPC [11]. Wheat straw ash and corncob ash were studied by Memon et al [12,13] and demonstrated good pozzolanic performance of the ash, aiding in the production of environmentally friendly concrete. Elephant grass ash (EGA) has been studied in terms of pozzolanic reactivity and the development of eco-friendly cements [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In short, researchers found the incorporation of agricultural and industrial waste suitable for the achievement of sustainable concrete as it has disposal problems and depletion of natural sand associated with it. It is worth mentioning that WSA has been previously used as a cement blend and composite [ 38 , 39 , 40 ]. The high concentration of amorphous silica in WSA induces pozzolanic reaction upon its incorporation in concrete [ 40 ], like that of other supplementary cementitious materials such as fly ash, ground granulated blast furnace slag and metakaolin as reported in the literature [ 41 ].…”
Section: Introductionmentioning
confidence: 99%